Student Creativity on TikTok: Building Public University Image Through Digital Content - Ahmad Rosikhul Fahmi; Zahra Dwi lugyn; M. Fahrizal Mufti Ash-Shidqi AD (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2025)
This study aims to explore how student creativity on TikTok can build the image of state universities through digital content. Using a qualitative descriptive approach, this study collected data from 200 UIN Malang students through a questionnaire. The results showed that 97.2% of students had seen content discussing campus life on TikTok, with 43.9% stating that the content influenced their educational choices. Further analysis showed that TikTok, as a social media platform, plays a significant role in shaping and strengthening positive perceptions of educational institutions, increasing engagement, and providing a significant influence on students' educational decisions.